Lumberjack Admission Test

Algebra Level 3

Chom them logs!

We need L amount of logs to build a bridge! How much is that, you ask? I'll give you a hint:

{ x 2 + x y + y 2 = a 2 log a x a + log b y b = a 3 \begin{cases} x^{ 2 }+xy+y^{ 2 }=a^{ 2 } \\ \log _{ \sqrt [ x ]{ a } }{ \sqrt { a } } +\log _{ \sqrt [ y ]{ b } }{ \sqrt { b } } =\frac { a }{ \sqrt { 3 } } \end{cases}

and

( x + y ) 2 a = L 3 \frac{(x+y)}{2a}=\sqrt{\frac{L}{3}}

So, how many logs do we need?


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

John M.
Aug 24, 2014

Let a x = u \sqrt [x ]{ a } =u , then

a = u x 2 \sqrt { a } =u^{\frac { x}{ 2 } }

log a x a = log u u x 2 = x 2 ; \log _{ \sqrt [ x ]{ a } }{ \sqrt { a } } =\log _{ u }{ u^{ \frac { x }{ 2 } } } =\frac { x}{ 2 };

equivalently,

log b y b = y 2 . \log _{ \sqrt [ y ]{ b } }{ \sqrt { b } } =\frac { y}{ 2 }.

Then, the second equation may be written as:

x 2 + y 2 = a 3 \frac { x }{2 }+ \frac { y}{2 }=\frac { a}{\sqrt{3} } .

Thus, we obtain the following system:

{ x 2 + x y + y 2 = a 2 ( 1 ) x + y = 2 a 3 ( 2 ) \begin{cases} x^2+xy+y^2=a^2 (1)\\ x+y=\frac { 2a}{\sqrt{3}} (2)\end{cases}

Squaring equation (2), we get

x 2 + 2 x y + y 2 = 4 a 2 3 ( 2 α ) x^2+2xy+y^2=\frac{ 4a^2 }{3 } (2\alpha) .

Subtracting (1) from (2 α ) \alpha) ,

x y = a 2 3 xy=\frac{a^2}{3} .

We arrive at the following system:

{ x + y = 2 a 3 x y = a 2 3 \begin{cases} x+y=\frac{2a}{\sqrt{3}}\\ xy=\frac{a^2}{3} \end{cases} .

And thus,

x = y = a 3 x=y=\frac{a}{\sqrt{3}}

Now to the problem:

( x + y ) 2 a = L 3 \frac{(x+y)}{2a}=\sqrt{\frac{L}{3}}

( a 3 + a 3 ) 2 a = L 3 \frac{(\frac{a}{\sqrt{3}}+\frac{a}{\sqrt{3}})}{2a}=\sqrt{\frac{L}{3}}

1 3 = L 3 \frac{1}{\sqrt{3}}=\sqrt{\frac{L}{3}}

L = 1 \boxed{L=1}

No need to solve for x x and y y or to use the first equation at all, since x + y = 2 a / 3 x+y = 2a/\sqrt{3} and x + y = 2 a L / 3 x+y = 2a \sqrt{L/3} . So L / 3 = 1 / 3 L/3 = 1/3 , so L = 1 L = 1 .

Patrick Corn - 6 years, 9 months ago

Log in to reply

Did the same way and was about to add this as solution.

Sajal Preet Singh Sethi - 6 years, 9 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...